(untitled) (Global Journal of Science Frontier Research, 2023)
The present study investigated cardiac oxidative status in carbon tetrachloride CCl4 -exposed rats treated with aqueous and ethanol extracts of Dialium guineense stem bark Adult male Wistar rats n 25 weighing 170 190 g mean weight 180 10 g were randomly assigned to five groups 5 rats per group normal control CCl4 control silymarin aqueous extract and ethanol extract groups With the exception of normal control the rats were exposed to CCl4 at a single oral dose of 1 0 mL kg body weight bwt Rats in the silymarin group were administered silymarin standard cardioprotective drug at a dose of 100 mg kg bwt while those in the two treatment groups received 1000 mg kg bwt of aqueous or ethanol extract orally for 28 days Activities of antioxidant enzymes such as catalase superoxide dismutase SOD glutathione peroxidase GPx and glutathione reductase GR were evaluated in heart homogenate The results showed that there were no significant differences in the concentrations of cardiac total protein TP among the groups p 0 05 The activities of the antioxidant enzymes and level of reduced glutathione GSH were significantly lower in CCl4 control group than in normal control group but they were increased by extract treatment p 0 05 However the level of cardiac malondialdehyde MDA increased by CCl4 intoxication was significantly reduced after treatment p 0 05 These results indicate that aqueous and ethanol extracts of D guineense stem bark may enhance antioxidant defense in rats hearts exposed to CCl4